2014
DOI: 10.1007/s11684-014-0363-x
|View full text |Cite
|
Sign up to set email alerts
|

An 84-month observational study of the changes in CD4 T-lymphocyte cell count of 110 HIV/AIDS patients treated with traditional Chinese medicine

Abstract: This study aimed to evaluate the therapeutic effect of traditional Chinese medicine (TCM) by observing the changes in CD4 T-lymphocyte cell count of 110 cases with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) treated continuously with TCM for 84 months. Information of 110 HIV/AIDS patients from 19 provinces and cities treated with TCM from 2004 to 2013 was collected. Changes in the indexes of CD4 counts ( ≤ 200, 201-350, 351-500 and > 500 cells/mm(3)) at five time points (0, 12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…A 7-year observational study suggested long-term use of CHM could maintain or slow the pace of CD4 cell counts declining. However, this study did not address bias, potential confounders and the possibility that results may have occurred by chance 9 . CHM has also been reported to relieve HIV/AIDS patients’ clinical symptoms (e.g., fatigue, pain, sleep disturbance, shortness of breath, coughing) and significantly decrease opportunistic infections in before and after studies 10–12 .…”
Section: Introductionmentioning
confidence: 95%
“…A 7-year observational study suggested long-term use of CHM could maintain or slow the pace of CD4 cell counts declining. However, this study did not address bias, potential confounders and the possibility that results may have occurred by chance 9 . CHM has also been reported to relieve HIV/AIDS patients’ clinical symptoms (e.g., fatigue, pain, sleep disturbance, shortness of breath, coughing) and significantly decrease opportunistic infections in before and after studies 10–12 .…”
Section: Introductionmentioning
confidence: 95%
“…CAM has been used to treat AIDS and its complications worldwide, including TCM, acupuncture, and Qigong. Several studies have shown that TCM can reduce drug side effects, improve the immune system, clinical symptoms, quality of life, and decrease mortality [4][5].Community-acquired pneumonia (CAP) is a major contributor to morbidity and mortality even in the current HIV treatment era, especially as patients age [6].Diarrhoea is one of the most common presenting complaints in HIV-infected patients. Since the rst AIDS cases were described, a high prevalence of gastrointestinal disturbance has been reported [7][8].Meanwhile, TCM is effective and safe for the treatment of asymptomatic AIDS [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…With a history of more than 5000 years, the clinical practice of traditional Chinese medicine (TCM) has become one of the main methods to supplement western medicine 6 . A number of studies have shown that TCM can help reduce the side effects of HAART, enhance patients' immunologic function, ameliorate clinical symptoms, and life quality 7,8 . Clinical studies have further shown that TCM has a positive impact on prolonging the life of HIV/AIDS patients, 9 indicating that TCM may become an effective complementary and alternative therapy for HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%